A Review on the Prevalence and Treatment of Antibiotic Resistance Genes in Hospital Wastewater - Lihua Lan; Yixin Wang; Yuxin Chen; Ting Wang; Jin Zhang; Biqin Tan (Toxics)
Antibiotic resistance is a global environmental and health threat. Approximately 4.95 million deaths were associated with antibiotic resistance in 2019, including 1.27 million deaths that were directly attributable to bacterial antimicrobial resistance. Hospital wastewater is one of the key sources for the spread of clinically relevant antibiotic resistance genes (ARGs) into the environment. Understanding the current situation of ARGs in hospital wastewater is of great significance. Here, we review the prevalence of ARGs and antibiotic-resistant bacteria (ARB) in hospital wastewater and wastewater from other places and the treatment methods used. We further discuss the intersection between ARGs and COVID-19 during the pandemic. This review highlights the issues associated with the dissemination of critical ARGs from hospital wastewater into the environment. It is imperative to implement more effective processes for hospital wastewater treatment to eliminate ARGs, particularly during the current long COVID-19 period.